Alteration in attention and cancer pain treatment - Kurita, Geana Paula; Pimenta, Cibele Andrucioli de Mattos; Oliveira Júnior, José Oswaldo de; Caponeiro, Ricardo (Revista da Escola de Enfermagem da USP, 2008)
Cognitive impairment can negatively impact daily routine. This fact encouraged the elaboration of this study, which analyzed the impact of pain treatment with opioids on attention. Patients were divided into groups that were given (n=14) and were not given opioids (n=12). Three interviews were conducted to assess attention using the Trail Making Test and the Digit Span Test. The groups were homogeneous regarding socio-demographic variables, pain and depression; they were not homogeneous regarding the Karnofsky scale and the use of adjuvant analgesics. The patients in treatment without opioids had better performance in the Digit Span Test - reverse order, in the second assessment (p=0.29); no differences were observed on the Trail Making Test. The observed impairments were limited, but while new studies do not confirm the findings, patients, professionals and caregivers must be alert about the possible deleterious effects of opioids on the cognitive function.